DEVELOPMENT OF RESEARCH COMPETENCE OF STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS ON THE BASIS OF INTER-SUBJECT APPROACH TO TRAINING - Pavel E. Shenderey; Evgeniy E. Shenderey; Iraida N. Romanova (Статистика и экономика, 2016)
Modern researches show that intersubject communications atinitial stages of their inclusion in cognitive activity of studentsplay a role of the situational starting, inducing incentive. The knowledge gained by students as a result of the previousexperience of assimilation of intersubject communicationsbecomes regulators of its informa-tive activity at any stage ofinclusion of intersubject communications in cognitive activityand developments of research competence.